MANTAINING BAHASA ANGKOLA BY ITS SPEAKERS AT LANGGAR COMMUNITY IN KOTA MEDAN - Armita Novriana Rambe (Universitas Negeri Medan, 2019)
The aims of this study was to investigate the strategies of Angkolanese maintain Bahasa Angkola at Langgar Community in Kota Medan. The research was conducted by using qualitative design. The data of this study were the utterances of Angkolanese speakers. There were 20 participants of this research. The data were collected through observation, questionnaire and interview. The result of this study revealed that: There were three factors that affecting language maintenance proposed by Fishman (1991) in this study namely family language policy, Using Angkola language in their daily communication frequently, and using Angkola language in cultural activity like in wedding ceremony. The using of these strategies can be applied to the first and second generation. Meanwhile the third generation found the difficulties when facing the strategies. They tend to use bahasa Indonesia in their daily life because most of their time are spending at school and they are not aware of the cultural activity around them.Key words: Strategies of Language Maintenance, Bahasa Angkola, Langgar Community.